A Grid Connected Photovoltaic Inverter with Battery-Supercapacitor Hybrid Energy Storage - Víctor Manuel Miñambres-Marcos (Sensors, 2017)
The power generation from renewable power sources is variable in nature, and may contain unacceptable fluctuations, which can be alleviated by using energy storage systems. However, the cost of batteries and their limited lifetime are serious disadvantages. To solve these problems, an improvement consisting in the collaborative association of batteries and supercapacitors has been studied. Nevertheless, these studies don’t address in detail the case of residential and large-scale photovoltaic systems. In this paper, a selected combined topology and a new control scheme are proposed to control the power sharing between batteries and supercapacitors. Also, a method for sizing the energy storage system together with the hybrid distribution based on the photovoltaic power curves is introduced. This innovative contribution not only reduces the stress levels on the battery, and hence increases its life span, but also provides constant power injection to the grid during a defined time interval. The proposed scheme is validated through detailed simulation and experimental tests.